Evaluation of NKT cells in vivo and in vitro in leprosy patients - Ilhan, F.; Godekmerdan, A.; Bulut, V. (My University, 2007)
Aim. In this study, the presence of NKT cells and their proliferation upon the addition of leprosy antigen in inactive leprosy patients was investigated. Forty (29 male 72.5%, 11 female 27.5%) inactive lepromatous leprosy patients, whose mean age was 60±2.28 years and thirty healthy subjects whose mean age was 45 ±3.48 years were evaluated. The mean duration of disease was 30.66±2.93 years. It was aimed to determine whether NKT cells were different in inactive leprosy patients and healthy subjects and these cells proliferate up-on the addition of leprosy antigen in inactive leprosy patients PBMC. Methods. Blood samples were collected, and a human NKT cell population that exhibits V?24 TCR subtype and NK activation marker CD161 were characterized by using flow cytometric analysis. Methods. Peripheral blood mononuclear cell (PBMC) cultures were analyzed for T, NK and NKT cells in patients. PBMC were stimulated in 24-well flat bottom plates with sonicated Mycobacterium leprae extract. Cells were harvested for flow cytometric analysis on 24 hour. Statistical analysis was done by using SPSS 11.0 and related sample T test for in vitro stimulated group and unrelated sample T test for patients and healthy subjects. For the statistical significance threshold, p<0.05 value was used. Results. The mean percent value of V?24+CD161+ NKT cells in blood samples was 0.92±0.21, which increased to 1.62±0.28 following stimulation (p<0.05). Conclusion. This result showed that NKT cells can play an important role on defense to M. leprae.
Keywords: Leprosy; NKT cells; V·24+CD161+